Kekuasaan sebagai Dasar Legitimasi Hukum dalam Pemikiran Filsafat Hukum - Seputra, Hawreyvian Rianda; Suyatno, Suyatno (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this research is to analyze the role of power as the basis of legal legitimacy in legal philosophy thought, as well as to examine the relationship between power and public acceptance of the law, including the ethical limits of the use of power in upholding legitimate and just laws. This research uses a qualitative approach with a literature review method, analyzing various legal philosophy thoughts from figures such as Thomas Hobbes, Max Weber, John Locke, and Immanuel Kant. The study focuses on how power becomes the main instrument that legitimizes law and ensures obedience and order in society. The results show that legitimate power recognized by society is a key element in legal legitimacy. Hobbes' thought underscores that without power, law has no power to compel compliance, while Locke emphasizes the importance of societal consent to the use of power. Weber added that power based on legality has the highest stability because it is based on rational rules. In terms of ethical limits, legal philosophy emphasizes that power should not be used arbitrarily and should be aligned with the principles of justice, human rights, and transparency. Thus, law can only function effectively and fairly if the power used to enforce it is governed by strong ethical norms and social justice.